2012
DOI: 10.7883/yoken.65.502
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methicillin-Resistant and Methicillin-Sensitive Staphylococcus aureus Strains Isolated from a Tertiary Hospital in Terengganu, Malaysia

Abstract: SUMMARY: Staphylococcus aureus is a persistent human pathogen responsible for a variety of infections ranging from soft-tissue infections to bacteremia. The objective of this study was to determine genetic relatedness between methicillin-resistant S. aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) strains. We isolated 35 MRSA and 21 MSSA strains from sporadic cases at the main tertiary hospital in Terengganu, Malaysia, screening them for the presence of virulence genes. Their genetic relatedness was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
33
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 43 publications
10
33
3
Order By: Relevance
“…In the present study, the incidence rate of the eta gene was higher than that reported in other studies from Iran 0.68% (12), Colombia (3%) (29), and Malaysia (0%) (6). Unlike the results of the present study, high prevalence of the eta gene was reported in studies conducted in Czech (10%) (5) and Turkey 19.2% (32).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…In the present study, the incidence rate of the eta gene was higher than that reported in other studies from Iran 0.68% (12), Colombia (3%) (29), and Malaysia (0%) (6). Unlike the results of the present study, high prevalence of the eta gene was reported in studies conducted in Czech (10%) (5) and Turkey 19.2% (32).…”
Section: Discussioncontrasting
confidence: 90%
“…The most prevalent toxin gene was found to be tst, with a prevalence rate of 51.4%, which is higher than that reported in previous studies conducted in Iran (11.6%) (12), Sweden (22%) (28), Malaysia (0.5%) (6) and Colombia (10%) (29). An interesting finding in the present study is that Arch Pediatr Infect Dis.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In the limited number of isolates studied, we were not able to define any specific correlation between clones and disease types. Although two studies have reported that no single staphylococcal genotype is specifically associated with a defined infection type (32,33), two other studies have shown CC5 and CC30 to be associated with infectious endocarditis and osteomyelitis (34,35).…”
Section: Discussionmentioning
confidence: 99%